Frequência de aplicação e diluição da solução nutritiva em cultivo de rúcula hidropônica - Santos, Jenyffer da Silva Gomes (2020)
The formulation of the nutrient solution is one of the most important points of hydroponic cultivation, since the absorption of ions from the nutrient medium is a selective and dynamic process, highlighting the relative proportion between nutrients in the solution. Thus, the experiment was conducted in a greenhouse in the Department of Agricultural Engineering of the Universidade Federal do Ceará, aiming to investigate the productive and nutritional efficiency, as well as the viability of a microcontroller regulating irrigation in association with the dilution of the nutrient solution recommended by Furlani. (1999) in the cultivation of hydroponic arugula. A randomized block design was used in a 5 X 2 split plot system scheme with 5 nutrient solution dilutions (20, 40, 60, 80 and 100%) and two irrigation frequencies based on different systems (analog timer and microcontroller with temperature), with four repetitions, totaling 40 experimental plots. Each hydroponic profile represents an experimental unit containing 98 plants. The hydroponics frequency regulator was designed, developed and tested during the design of the experiment. The variables analyzed in the experiment are: Biometric measurements (fresh and dry shoot weight, leaf area, leaf area index, leaf numbers, plant height), macronutrient leaf contents (N, P, K, Ca, Mg and S) and leaf gas exchange. Data were subjected to analysis of variance and then when significant to the F Test, subjected to regression analysis. It was observed for production and nutritional analysis significant difference between cycles. For the growth measures in both cultivation cycles, all the variables studied were influenced in different ways both by the isolated factors and by the interaction between them, except for the number of leaves, which was not influenced in any of the studied cycles. For gas exchange, the variables of the first and second cycle did not show significant effect. Regarding physiological aspects, the 20% dilution is more efficient. Regarding nutritional analysis, the second cycle presented a better quadratic adjustment, showing an increase in the concentration of P as the electrical conductivity of the nutrient solution increased. Further testing with the equipment is suggested to prove its true efficiency.